2018
DOI: 10.1002/mame.201800531
|View full text |Cite
|
Sign up to set email alerts
|

Combination Intumescent and Kaolin‐Filled Multilayer Nanocoatings that Reduce Polyurethane Flammability

Abstract: Chitosan (CH), ammonium polyphosphate (APP), CH and poly(acrylic acid) (PAA)‐stabilized kaolin (KAO) clay are deposited as quadlayers onto the surface of flexible polyurethane foam (PUF) via layer‐by‐layer assembly in order to improve the fire resistance of the foam. The effectiveness of this nanocoating on flame suppression is compared to control films without KAO and bilayer coatings. PUF coated with only five CH/APP/CH/PAA‐KAO quadlayers (around 184 nm thick) maintains its open porous structure and self‐ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 44 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…The 1 wt% APP was added into DI water and the PH value was adjusted according to previous literature. [13] APP solution was used for deposition immediately upon preparation. [17]…”
Section: Preparation Of Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 1 wt% APP was added into DI water and the PH value was adjusted according to previous literature. [13] APP solution was used for deposition immediately upon preparation. [17]…”
Section: Preparation Of Solutionsmentioning
confidence: 99%
“…The incorporation of intumescent coating and melamine slightly increase the smoke generation of the fabric in the heat radiation process, which has been observed in the previous work. [13] The reason can be attributed to the incorporation of flame retardant coating leads to an intumescent char formation in the condensed phase, which acts as a protective layer on the surface of the PET-COT matrix and causes incomplete combustion. Besides, the addition of MEL can also release inflammable gases.…”
Section: Smoke Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its unique porous structure and organic constituents, FPUF contains the DOI: 10.1002/mame.202100930 main trigger conditions of the dangerous conflagration which are larger ignition area and flammable components. [7][8][9] Even, oneroom setting with furniture and bedding which are filled with FPUF is capable of occurring flashover once ignited. [5] Hence, it fails to meet the requirements of materials used in higher fire-safety occasions.…”
Section: Introductionmentioning
confidence: 99%
“…This particular structure has been proved to significantly increase the flame retardancy of PU foams due to a combined effect of heat shielding/reradiating and delayed release of combustible volatiles [25,26]. Although most of the developed coatings have been focused on the exploitation of mineral nanoplates such as montmorillonite [25], vermiculite [27] and kaolinite [28], recent reports showed that oxidized graphitic materials can endow superior flame-retardant properties [21]. Indeed, it has been demonstrated that an LbL coating comprising of six bi-layers (BLs) alternating chitosan (CHIT) and graphite oxide (GO) nanoplates can improve the flame retardancy of PU foams by limiting the flaming ignition in forced combustion tests and suppressing the melt-dripping phenomenon during flammability tests [22].…”
Section: Introductionmentioning
confidence: 99%